2011
DOI: 10.2135/cropsci2010.06.0327
|View full text |Cite
|
Sign up to set email alerts
|

General Resistance in Maize to Southern Rust (Puccinia polysora Underw.)

Abstract: Southern corn rust (Puccinia polysora Underw.) is a major tropical disease that can iead to severe yield losses in the tropics. Occasionally it becomes of concern in temperate regions, as in 2010. We summarize 45 yr of research on the occurrence, genetic basis, and breeding of general resistance. Trials were conducted in Colombia, Hawaii, Nigeria, the Philippines, Texas, and Thaiiand. Temperate maize proved uniformly susceptible. No racially specific monogenes were effective. Resistance varied continuously amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 34 publications
0
57
0
Order By: Relevance
“…Heritability percentage of our mapping populations were categorized in high level [58]. The heritability of resistance for southern corn rust in maize has been studied and reported previously: 79% -86% [36], 93% [37], 51% -66% [12], and 53% -68% [59]. We concluded that the inheritance of resistance for southern corn rust was attributable to the influence from genotypic variation more than environmental variation (V P = V G /V E ).…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Heritability percentage of our mapping populations were categorized in high level [58]. The heritability of resistance for southern corn rust in maize has been studied and reported previously: 79% -86% [36], 93% [37], 51% -66% [12], and 53% -68% [59]. We concluded that the inheritance of resistance for southern corn rust was attributable to the influence from genotypic variation more than environmental variation (V P = V G /V E ).…”
Section: Discussionmentioning
confidence: 84%
“…The disease has emerged in Thailand since 1967 [12] it caused a severe damage of corn varieties in Nakhonratchasima, Saraburi and Tak provinces. Biodiversity and classification of the pathogens in Thailand were studied using morphology and molecular markers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under the quantitatively resistance model, recurrent selection would be the most appropriate breeding method for improving tolerance. Indeed, several studies have documented significant gains from recurrent selection for NCLB resistance (Brewbaker et al, 2011;Campaña and Pataky 2005;Carson 2006;Ceballos et al, 1991;Jenkins et al, 1954;Pataky 1994) with 15 to 20% reduction in susceptibility per generation (Campaña and Pataky 2005;Carson 2006;Ceballos et al, 1991).…”
Section: Resultsmentioning
confidence: 99%
“…One tolerant hybrid to NCLB with sustainable yield potential is better than ten hybrids with several single gene controlled race specific high resistance, most of them will be broken down one day. This principle can be applicable universally, particularly under climate change (Brewbaker et al, 2011;Kim et al, 2008).…”
Section: Resultsmentioning
confidence: 99%